You are on page 1of 5

TRIGONOMETRY FUNCTION

SECTION-A
1)
2)
3)
4)
5)
6)
7)
8)
9)

l = rθ
1 radian = (180)◦
π

1 = ( π ) radian
180
Sin (2nπ + x) = Sinx
Cos (2nπ + x) = Cosx
Tan (nπ + x) = Tanx
Sec (2nπ +x) = Secx
Cosec (2nπ + x) = Cosecx
Cot (nπ + x) = Cotx

10) Sinx = 0

x = nπ , n ∈ Z

11)

Cosx = 0

x = (2n + 1)π , n ∈ Z

12)
13)
14)
15)
16)

Sin x + Cos x = 1
1 + Tan2x = Sec2x
1 + Cot2x = Cosec2x
Sin (-x) = -Sinx
Cos (-x) = Cosx
2

2

π
± ,
2

2

π± ,

Sinθ = Sinθ

2π ±

Cosθ = Cosθ
Tanθ = Tanθ


±
2

Cotθ = Cotθ

Sinθ = Cosθ

Secθ = Secθ

Cosθ = Sinθ

Cosecθ = Cosecθ

Tanθ = Cotθ
Cotθ = Tanθ

SECTION-B

Secθ = Cosecθ
1) Cos (x + y) = Cosx Cosy – Sinx Siny
Cosecθ = Secθ

2) Cos (x – y) = Cosx Cosy + Sinx Siny 3) Sin (x + y) = Sinx Cosy + Cosx Siny 4) Sin (x – y) =Sinx Cosy – Cosx Siny 5) Tan (x + y) = tanx + tany 1 .tanx tany 6) Tan (x – y) = tanx .tany 1 + tanx tany 7) Cot (x + y) = Cotx Coty .1 Coty + Cotx 8) Cot (x – y) = Cotx Coty + 1 Coty – Cotx 9) Sin 2x = 2Sinx Cosx = 2 tanx 1 + tan2x 10) Cos 2x = Cos2x .Sin2x = 1 – 2Sin2x = 2Cos2x – 1 = 1 – tan2x 1 + tan2x 11) Cot 2x = Cot2x – 1 2Cotx 12) Tan 2x = 2tanx 1 – tan2x .

13) Sin 3x = 3Sinx – 4Sin3x 14) Cos 3x = 4Cos3x – 3Cosx 15) Tan 3x = 3tanx – tan3x 1 – 3tan2x 16) Cot 3x = Cot3x – 3Cotx 3Cot2x – 1 17) Cos (x + y) + Cos (x – y) = 2Cosx Cosy 18) Cos (x + y) – Cos (x – y) = -2Sinx Siny OR Cos(x – y) – Cos(x + y) = 2Sinx Siny 19) Sin (x + y) + Sin (x – y) = 2Sinx Cosy 20) Sin (x + y) – Sin (x – y) = 2Cosx Siny 21) Cosx + Cosy = 2Cos (x + y) Cos (x – y) 2 2 22) Cosx – Cosy = -2Sin (x + y) Sin (x – y) 2 2 23) Sinx + Siny = 2Sin (x + y) Cos (x – y) 2 2 24) Sinx – Siny = 2Cos (x + y) Sin (x – y) 2 25) Sinx = 2Sin x/2 Cos x/2 = 2tan x/2 1 + tan2x/2 26) Cosx = Cos2x/2 .Sin2x/2 = 1 – 2Sin2x/2 2 .

x = nπ + (-1)n y 36) Cosx = Cosy. x = 2nπ ± y 37) Tanx = Tany.= 2Cos2x/2 – 1 = 1 – tan2x/2 1 + tan2x/2 27) Tanx = 2tanx/2 1 – tan2x/2 28) Cotx = Cot2x/2 – 1 2Cotx/2 ± √ 1−cos 2 x 2 30) Cosx = ± √ 1+cos 2 x 2 ± √ 1−cos 2 x 1+cos 2 x 29) Sinx = 31) Tanx = √ 1−Cosx 2 = ± √ 1+Cosx 2 ± √ 1−Cosx 1+Cosx 32) Sin x 2 = ± 33) Cos x 2 34) Tan x 2 = 35) Sinx = Siny. x = nπ + y 38) Sine rule a Sin a = b Sin b 39) Cosine rule = c Sin c =k .

a) CosA = b2 + c2 – a2 2bc b) CosB = a2 + c2 – b2 2ac c) CosC = a2 + b2 – c2 2ab 40) Sin (A + B) Sin (A – B) = Cos2B – Cos2A = Sin2A – Sin2B 41) Cos (A + B) Cos (A – B) = Cos2B – Sin2A = Cos2A – Sin2B 42) Sin (A + B) Cos (A – B) = SinA CosA + SinB CosB 43) Cos (A + B) Sin (A – B) = SinA CosA – SinB CosB .